SCIENCE FICTION FILM GENRE AS GEOPROSPECTIVE TOOL FOR CITIES. - Quílez Aznar, Nacho; Pueyo Campos, Ángel (Geographicalia, 2022)
Science fiction film productions have become a very powerful tool to predict and illustrate societal and territorial threats and, in particular, to visualise future urban models. It is common knowledge that cinema is a powerful instrument to spread and envisage how future cities might look like. Therefore, beyond being such a great source of entertainment, there is no denying that films allow us to create and disseminate not only the main theories and complex thoughts, but also the analysis of the most accessible ideological and philosophical trends. Hence, the aim of this essay is to analyse the strong and underlying bond between human geography and cinema. For that purpose, a set of science fiction films is listed and evaluated through a geoprospective study which ultimately allows us to present a deep reflection regarding the future of our societies and its urban models, and the disagreement with the present.
Keywords: Science fiction; Geoprospective; Future; Urban areas; Ideal cities; ODS